Finite element parametric study of the split sleeve cold expansion on residual stresses and pulling force. (March 2022) - Dey, Mithun K; Kim, Dave; Tan, Hua
Split sleeve cold expansion (SSCE) is a crucial cost-effective process to improve the fatigue life of metallic structures with holes in the aerospace industry. In this study, the effects of the workpiece material's yield strength (290.9 MPa to 377.8 MPa) and the applied SSCE expansion percentage (3.330% to 4.377%) on mandrel pulling force and residual stresses were investigated numerically for aluminum 2024-T351. A three-dimensional finite element (FE) model was developed to simulate the SSCE process using a commercial FE software, ABAQUS. The model geometries, material non-linearities, and contact conditions were adopted according to aerospace industrial applications' standards. After the numerical model was validated with the published data, a parametric study with variable material properties and expansion percentage was conducted using the FE model. Our parametric study shows that an increase in both the Al workpiece's yield strength and SSCE expansion percentage can improve the induced residual stresses in the hoop direction around the cold expanded hole; however, the workpiece's yield strength has a higher impact on the residual stress field. The in-process pulling force during the SSCE process increases with increasing workpiece yield strength and expansion percentage.